The Effects af Communicative Language Teaching and Brain Functioning Upon Students’ Speaking Skills - Nugroho Nugroho (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
The purpose of this study was to determine the effects of communicative language teaching and brain functioning upon student’s speaking skill, to determine the influence of communicative language teaching upon student’s speaking skill, and to determine the influence of brain dominance upon student’s speaking skill. The research method used is experimental method. Samples were taken as many as 40 students with a simple random technique. The data was collected by distributing questionnaires directly to the sample. Data analysis using descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics is to look for simple and multiple correlation coefficients followed by significance test of correlation coefficient with a t test. The results showed: 1) there is a significicant influence of brain dominance upon the student’s speaking skill Fobserved = 5.23 > Ftable = 4.49, 2) there is a significant influence of communicative language teaching upon students’ speaking skill Fobserved = 7.08 > Ftable = 4.49, 3) there is significant interaction of communicative language teaching and brain functioning upon student’s speaking skill Fobserved = 48.64 > ftable =8.53 Key Words: Brain Functioning, Communicative Language Teaching, Speaking Skill